Musical expression in the lieder of Hugo Wolf - Tichart, Victor Hugo (African Cinema Unit, 2025)
Gesamtkunstwerk by unifying all the aspects of opera into one holistic creation, so Wolf unified the text, vocal line and piano part of the Lied, bringing it to its zenith in the history of music. Ultimately, though, the aim of this thesis is to assist those performing Wolf's Lieder in gaining an understanding of both individual Lieder and Wolf's style as a whole, enabling them to analy se the Lieder for themselves.